Determinants of Growth of Supermarkets in Sri Lanka - Karunaratne, H.D. (My University, 2012)
The number of supermarkets has been rapidly growing in Sri Lanka during the recent past. This study attempts to identify determinants of such growth. There are four main objectives of this paper, namely (i) to understand the factors which are considered in establishing the supermarket outlets;(ii) to understand the factors which determine their growth; (iii) to understand how supermarkets can increase profits by minimizing social and economic externalities; and (iv) to understand how consumers can be better off by using supermarkets. In order to achieve these objectives, this study present SWOT of supermarkets, analyzing the growing trends of supermarkets, socio-economic characteristics, family consumption patterns and income and expenditure patterns of supermarket shoppers. This study utilized both published and unpublished macro and micro level data. The primary data was obtained by means of conducting in-depth interviews and two surveys. Secondary data was collected from the survey findings published by the Central Bank of Sri Lanka. According to the facts established by means of analysing the data collected, a strong relationship was found between the two variables, growth of supermarkets and the emerging consumer behaviour patterns in Sri Lanka. Further, the study revealed a clear change of the patterns of consumer behaviour associated with the expansion of supermarkets. Finally, interdependent relationship between the growth of supermarkets and emerging patterns of consumer behaviour was identified in the context of urban Sri Lanka.